Brief Survey of Biological Network Alignment and a Variant with Incorporation of Functional Annotations - Jing, Fang; Zhang, Shao-Wu; Zhang, Shihua (Current Bioinformatics, 2019)
Background: Biological network alignment has been widely studied in the context of protein-protein interaction (PPI) networks, metabolic networks and others in bioinformatics. The topological structure of networks and genomic sequence are generally used by existing methods for achieving this task. Objective and Method: Here we briefly survey the methods generally used for this task and introduce a variant with incorporation of functional annotations based on similarity in Gene Ontology (GO). Making full use of GO information is beneficial to provide insights into precise biological network alignment. Results and Conclusion: We analyze the effect of incorporation of GO information to network alignment. Finally, we make a brief summary and discuss future directions about this topic.
Keywords: optimization